The Role of Consumer-cause Identification and Attitude in the Intention to Purchase Cause-related Products - Duarte, Paulo (2018)
Purpose – The purpose of this paper is to extend prior research on the influence of consumer-cause identification on the intention to purchase products from the companies supporting the cause and re-evaluates the role of attitude toward the cause as a mediator of the relationship between identification and intention to purchase. Design/methodology/approach – Using a questionnaire, a sample of 156 Portuguese consumers evaluated their personal identification and attitude to one of four causes. Partial least squares path modeling was used to evaluate the proposed conceptual model. Findings – The results reveal that more than identification, a positive attitude is vital to be able to predict the intention to purchase. Together, consumer-cause identification and attitude explain 35.1 percent of the variance in purchase intention. The findings show also that attitude acts as a mediator in the relationship between the identification with the cause and intention to purchase. Several differences regarding gender and age are also revealed. Originality/value – While the majority of studies were single cause evaluations, the current results are based on the assessment of multiple causes. Consequently, the findings are more comprehensive and robust, providing important insights to researchers. The conclusions confirm within a wider context the role of attitude as a mediator of the identification and intention to purchase and can further assist companies in designing better targeted cause-related marketing campaigns.